Telemetring of Water Level of Dam in Real Time System (International Journal of Psychosocial Rehabilitation, 2020)
The dam on PLTA (hydropower plant) has a function as water supply of primary power needed in PLTA, so that the water level in dam is really impact in operating the Generator Unit. Nowadays, some PLTA are still using conventional method to monitor the dam level by means of using manual measuring instrument where is placed on the edge of dam. In fact, level monitoring conventionally is not effective and efficient because it is not monitored in real time. Level monitoring conventionally causes operating of the Generator Unit only guessing the exitance of the water level. It has an effect if the water level goes down, it will impact to the instrument breakdown in Generator Unit because there is many dirt. With the result that is made an instrument of prototype of telemetering dam level via mobile phone based on NodeMcu ESP 8266 so the water level can monitor in real time and facilitate in operating the Generator Unit in low level or high level